1979
DOI: 10.1111/j.1600-051x.1979.tb02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of inflamed gingival surfaces

Abstract: Abstract. The present study was undertaken to clarify whether visual inflammation or gingival bleeding on probing is the earlier indicator of gingivitis. A dental prophylaxis was given to 90 male students and 1 month later the gingiva adjacent to the mesio‐buccal, mid‐buccal and mid‐lingual surfaces of all teeth was evaluated. Two subsequent examinations were done at 1‐month intervals. Each gingival margin was examined visually and classified as either non‐inflamed or inflamed and these same surfaces were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…Although BOP measures are routinely carried out at dental clinical examination, BOP has not been given much attention. Gingival bleeding after stimulation of the gingival sulcus or pocket has been found to be associated with periodontal inflammation in clinical, histopathological and bacteriological aspects of the disease. Regarding the inherent ability of BOP to distinguish the disease condition, previous studies have reported a low sensitivity, but high specificity, of this measurement.…”
Section: Discussionsupporting
confidence: 83%
“…Although BOP measures are routinely carried out at dental clinical examination, BOP has not been given much attention. Gingival bleeding after stimulation of the gingival sulcus or pocket has been found to be associated with periodontal inflammation in clinical, histopathological and bacteriological aspects of the disease. Regarding the inherent ability of BOP to distinguish the disease condition, previous studies have reported a low sensitivity, but high specificity, of this measurement.…”
Section: Discussionsupporting
confidence: 83%
“…BOP is easily detected clinically and, therefore, is of value for the early diagnosis and prevention of more advanced gingivitis. It was shown that BOP appeared earlier than a change in color or other visual signs of inflammation 40 . Because BOP was associated with viruses in healthy sites, BOP positivity can be interpreted as an early indication of inflammation rather than the GI, which is a visual indication of gingival inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the bleeding from interproximal tissue is more likely to originate from inflamed connective tissue in mid-interproximal areas where visibility is obscured (Meitner et al 1979, Abrams et al 1984, Amato et al 1986). Bleeding points in the gingivae do not correlate directly with clinical inflammation but rather precede apparent inflammation (Lenox & Kopczyk 1973).…”
Section: Bleeding On Flossingmentioning
confidence: 99%